The Dynamics of the Impact of Public Expenditure on Economic Growth for the Period (1990-2021) - The Tunisian Model - Muthna Shakor Mahmood; Sonia Ghorbel Zouari (Migration Letters, 2023)
Public expenditure is a crucial determinant that exerts a substantial influence on the trajectory of economic growth. The concept in question has undergone a transformation within the domain of economic discourse, with numerous scholarly works dedicated to examining this phenomena. Public expenditure is a complex and multifaceted concept that encompasses a range of theoretical and practical dimensions. The prevailing consensus among economists in characterizing public expenditure is the phenomenon of inflation, characterized by a sustained and significant rise in prices. Hence, employing the term "public expenditure" in the absence of specific contextual parameters or phenomena suggests an escalation in costs. Nevertheless, it is important to note that not all instances of price increases can be solely attributable to governmental expenditure. The core focus of inquiry pertains to the impact of public expenditure on the rate of economic growth. To clarify, does the allocation of public funds have a discernible influence on the rate of economic growth in Tunisia within the time span of 1990 to 2021? Can inflation have a positive impact on the economic growth rates in Tunisia? The research hypothesis suggests a positive relationship between public expenditure and the economic growth rate in Tunisia throughout the period from 1990 to 2021. The study yielded multiple findings, with the primary one being that both the main variable (government expenditure) and the dependent variable (economic growth) exhibited non-stationarity at the initial level, as indicated by their significant probability exceeding 5%. In each of the situations (With Constant, With Constant & Trend, Without Constant & Trend), the variables were not integrated at the zeroth order. The test findings suggest that all variables exhibit stationarity after being differenced once. This implies that the independent variable (government expenditure) as well as the dependent variable (economic growth) exhibited stationary behavior at the initial difference, as indicated by their probability values being below 5% across all scenarios (With Constant, With Constant & Trend, Without Constant & Trend).